Molluscum contagiosum with atopic dermatitis: a clinical retrospective study of 2,278 children - Li, Tingying; Gao, Nan; Zeng, Zilu; Fu, Guili (Frontiers in Pediatrics, 2025)
ObjectiveThe dissemination of Molluscum contagiosum (MC), a prevalent pediatric cutaneous viral infection, is enhanced upon atopic dermatitis (AD) or compromised epidermal barrier function. However, the potential influence of AD on the course of MC remains controversial. This study aimed to evaluate the influence of AD on MC treatment outcomes.MethodsIn this clinical retrospective study, we enrolled children with MC and divided them into control (patients with MC alone) and observation (patients with both MC and AD) groups. Parameters such as sex, age, treatment sessions, and treatment duration were recorded for all patients. Efficacy endpoints were defined as complete clearance, with no further MC treatment required for half a year. Chi-squared and Z-tests were performed to compare the clinical and demographic parameters between the groups.ResultsAmong 2,278 patients, 1,931 (84.77%) had MC alone, and 347 (15.23%) had concurrent MC and AD. Significant differences were observed in treatment sessions (p < 0.05) between the two groups. However, sex, age, and treatment duration did not differ significantly between the groups (p > 0.05).ConclusionAD increased the number of treatment sessions of MC in children but was not closely related to sex, age, or treatment duration.